2017
DOI: 10.1038/srep43094
|View full text |Cite
|
Sign up to set email alerts
|

3D characterization of morphological changes in the intervertebral disc and endplate during aging: A propagation phase contrast synchrotron micro-tomography study

Abstract: A better understanding of functional changes in the intervertebral disc (IVD) and interaction with endplate is essential to elucidate the pathogenesis of IVD degeneration disease (IDDD). To date, the simultaneous depiction of 3D micro-architectural changes of endplate with aging and interaction with IVD remains a technical challenge. We aim to characterize the 3D morphology changes of endplate and IVD during aging using PPCST. The lumbar vertebral level 4/5 IVDs harvested from 15-day-, 4- and 24-month-old mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Degeneration of the intervertebral disc occurs due to morphological and histological changes to the intervertebral discs, as well as changes in the molecular biology of the NP, which are induced by internal and external factors (26). The proliferation and apoptosis of NP cells and the abnormal metabolism of the extracellular matrix components are key causes of intervertebral disk degeneration (27).…”
Section: Discussionmentioning
confidence: 99%
“…Degeneration of the intervertebral disc occurs due to morphological and histological changes to the intervertebral discs, as well as changes in the molecular biology of the NP, which are induced by internal and external factors (26). The proliferation and apoptosis of NP cells and the abnormal metabolism of the extracellular matrix components are key causes of intervertebral disk degeneration (27).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that excessive pressure may result in disc degeneration, while moderate pressure is beneficial for the repair of intervertebral disc [5,6,17,18]. However, the signaling pathways initiated by mechanical stress and the relevant thresholds have not been precisely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Calcification of the cartilage endplate significantly reduces the nutrient levels and excretion of metabolites in human IVD [4]. Previous studies have shown that IVD degeneration may originate from endplate change [5][6][7]. We thought the cartilage endplate was disturbed by hydrostatic pressurization in human IVD.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the biomechanical elements, which are represented by unbalanced mechanical loading [14], genetic background [15] and reduced cellular activity, lead to continuous structural failure ( Figure 1) [16]. In terms of biochemical changes, the deficiency in nutrient diffusion into the disc due to the calcified cartilaginous endplate (CEP) is a fundamental cause of IVD degeneration [17]. Additionally, increased elastin concentrations in the annulus fibrosus (AF) [18], and augmented proteoglycan breakdown in the nucleus pulposus (NP) cause a dramatic decrease in disc height and ultimately lead to biomechanical instability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2020, 10, x FOR PEER REVIEW 2 of 24 fundamental cause of IVD degeneration [17]. Additionally, increased elastin concentrations in the annulus fibrosus (AF) [18], and augmented proteoglycan breakdown in the nucleus pulposus (NP) cause a dramatic decrease in disc height and ultimately lead to biomechanical instability [19].…”
Section: Introductionmentioning
confidence: 99%